Assessing the Impact of Neurogenic Claudication on Outcomes Following Decompression With Lumbar Interbody Fusions in Patients With Lumbar Spinal Stenosis. Issue 2 (March 2021) - Martini, Michael L.; Nistal, Dominic A.; Deutsch, Brian C.; Neifert, Sean N.; Lamb, Colin D.; Caridi, John M.
Study Design: Retrospective cohort study. Objectives: To conduct the first comprehensive national-level study examining specific risks, outcomes, and costs surrounding surgical treatment of lumar spinal stenosis (LSS) in patients with and without neurogenic claudication (NC). Methods: Data for patients with or without NC who underwent decompression with a lumbar interbody fusion approached anteriorly (ALIF), posteriorly (PLIF), or laterally (LLIF) for LSS was collected from the 2013-2014 National Inpatient Sample using International Classification of Disease codes. Results: A total of 121 025 LSS cases without NC and 20 095 cases with NC were included in this study. The most significant complications associated with NC status by organ system included renal ( P = .0030) and hematological complications ( P = .0003). Multivariate regression controlling for key demographic and comorbidity variables showed that patients with NC did not have significantly higher odds of complication, non-home discharge, or extended hospitalization compared to patients without NC regardless of fusion type. Interestingly, NC patients had comparatively lower total charges for their hospitalization following PLIFs ( P = .0001) and LLIFs ( P < .0001), but not ALIFs ( P = .6121). Conclusion: NC does not appear to significantly increase odds of adverse outcomes following fusion in LSS. Given the large prevalence of LSS and coincidental NC, these findings may carry important implications in managing this challenging patient population and justifies future prospective investigation of this topic.